2020
DOI: 10.1083/jcb.201911126
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate is a clearance receptor for aberrant extracellular proteins

Abstract: The accumulation of aberrant proteins leads to various neurodegenerative disorders. Mammalian cells contain several intracellular protein degradation systems, including autophagy and proteasomal systems, that selectively remove aberrant intracellular proteins. Although mammals contain not only intracellular but also extracellular proteins, the mechanism underlying the quality control of aberrant extracellular proteins is poorly understood. Here, using a novel quantitative fluorescence assay and genome-wide CRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 65 publications
2
48
0
1
Order By: Relevance
“…Human clusterin is considered an extracellular chaperone that can bind to misfolded proteins and then undergo degradation. A recent study revealed the mechanisms by which clusterin clears misfolded proteins: clusterin binds to heparan sulfate through electrostatic interaction, is transported into the cell through the heparan sulfate receptor on the cell surface and then is degraded in lysosome [ 36 ]. This pathway could promote the degradation of amyloid beta peptide, which explains why clusterin is associated with Alzheimer's disease [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Human clusterin is considered an extracellular chaperone that can bind to misfolded proteins and then undergo degradation. A recent study revealed the mechanisms by which clusterin clears misfolded proteins: clusterin binds to heparan sulfate through electrostatic interaction, is transported into the cell through the heparan sulfate receptor on the cell surface and then is degraded in lysosome [ 36 ]. This pathway could promote the degradation of amyloid beta peptide, which explains why clusterin is associated with Alzheimer's disease [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Clusterin mediates the clearance from the plasma (via the liver and kidney) and CSF (via transcytosis across the blood–brain barrier (BBB) of a variety of client proteins ( Figure 2 , panel 1). Clusterin also promotes endocytosis and degradation via non-professional phagocytic cells, through binding cell surface HSPGs ( Itakura et al, 2020 ) ( Figure 2 , panel 2) and via microglial cells by binding the surface receptor TREM2 (Triggering Receptor Expressed on Myeloid Cells 2) ( Yeh et al, 2016 ) ( Figure 2 , panel 3). Similar membrane receptors in brain cells promote extracellular clearance of client-chaperone complexes.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , clusterin promotes transcytosis of Abeta across the blood–brain barrier through [lipoprotein-related protein 2 (LRP2)-mediated endocytosis] ( Zlokovic, 1996 ; Wojtas et al, 2017 ). More broadly, clusterin has been shown to promote internalization and degradation of cellular debris and misfolded proteins in non-professional phagocytic cells through LRP2 ( Bartl et al, 2001 ) and through HSPGs ( Itakura et al, 2020 ). Itakura et al (2020) demonstrated that clusterin binds HSPGs through an electrostatic interaction to promote co-degradation of clusterin and client proteins.…”
Section: Clusterinmentioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanisms of intracellular protein quality control are well known, the quality control machinery for extracellular proteins, which are subjected to more stringent environmental conditions, is largely hidden in a veil of mystery. In the current issue, Itakura et al identified a mechanism by which aberrant extracellular proteins are transported into cells in a receptor-mediated manner to degrade them in the lysosome (1).…”
mentioning
confidence: 99%